(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
This study draws on belonging to the categories of listed ingredients and listed tribes commonly referred to as SCST and the role of reservation policy to see the impact of enforcement. Implementing this policy in higher education in India, with respect to the act of embryos. Reservations are only an important means of promoting equality for the weakest sections of society. First we must understand the true meaning of equality itself. What is important here is that the Indian regime ensures equality of the weaker sections of society and the approach of the Supreme Court of India is liberal in interpreting the equality provisions of the constitution. Indian law.